Debulking of giant liver hemangiomas with severe symptoms: a case report - Shun-ichi Ariizumi; Yoshihito Kotera; Shingo Yamashita; Akiko Omori; Takaaki Kato; Go Shibuya; Hiroto Egawa; Masakazu Yamamoto (Surgical Case Reports)
Abstract Background There are no previous reports of debulking of giant liver hemangioma. This report describes our experience with debulking surgery for a patient with bilateral giant liver hemangiomas with severe symptoms. Case presentation We present a case of symptomatic giant liver hemangioma in a 41-year-old woman. She presented with abdominal pain and fullness at a local hospital and underwent trans-arterial embolization (TAE). TAE was not effective, and she was not able to walk a long distance. Giant liver hemangiomas, 30 cm and 15 cm in diameter, were located in the right liver and in the left lateral section, respectively, and normal liver parenchyma with tiny liver hemangiomas was present in segment 4. The liver function was normal. However, right hemi-hepatectomy with left lateral sectionectomy was considered to be risky according to the 3DCT volumetry. Therefore, we performed right hemi-hepatectomy in order to reduce her symptoms. The postoperative course was uneventful, and she was discharged on the 14th day after surgery. The abdominal fullness and abdominal pain disappeared immediately after surgery. The hemangiomas in the remnant liver, 15 cm in diameter, showed no change, and she is well without symptoms 7 years after surgery. Conclusions Debulking surgery is one of the options for bilateral giant liver hemangiomas with severe symptoms.